2020
DOI: 10.3390/ijms21124501
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Review of Pro- and Anti-Inflammatory Properties of Plasma Lysophosphatidylcholines in the Vascular System

Abstract: Lysophosphatidylcholines are a group of bioactive lipids heavily investigated in the context of inflammation and atherosclerosis development. While present in plasma during physiological conditions, their concentration can drastically increase in certain inflammatory states. Lysophosphatidylcholines are widely regarded as potent pro-inflammatory and deleterious mediators, but an increasing number of more recent studies show multiple beneficial properties under various pathological conditions. Many of the discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 175 publications
(179 reference statements)
7
88
0
Order By: Relevance
“…It has been demonstrated that the acyl chain length and saturation may impact biological activity and function of different LPCs 22 and this may explain the different patterns found by us in our study. Some authors have suggested that the modulation of host glycerophospholipid metabolism is to support virus replication [23][24][25] , but most importantly, LPCs have been recognized as important homeostatic mediators involved in in ammation and activation of immune cells 26 . LPCs have been found to act as a strong chemoattractant for monocytes, T cells, as well as natural killer (NK) cells, attracting them to sites of in ammation 26 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the acyl chain length and saturation may impact biological activity and function of different LPCs 22 and this may explain the different patterns found by us in our study. Some authors have suggested that the modulation of host glycerophospholipid metabolism is to support virus replication [23][24][25] , but most importantly, LPCs have been recognized as important homeostatic mediators involved in in ammation and activation of immune cells 26 . LPCs have been found to act as a strong chemoattractant for monocytes, T cells, as well as natural killer (NK) cells, attracting them to sites of in ammation 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the effects of LPC on immune cells are contradictory [ 135 ]. Specifically, most older studies investigating the effects of LPCs on eosinophils found them to be pro-inflammatory–increasing the activation, adhesion, and migration of eosinophils [ 115 , 116 ].…”
Section: Phospholipases Play a Key Role In Allergiesmentioning
confidence: 99%
“…Although there are some phenomena that cannot be directly explained by the redox state, for example, the concentration of LPC in the plasma (strongly inversely correlated with soft stool) increases in certain in ammatory conditions, but recently there have been reports that a decrease in plasma LPC concentration worsens the disease 53 . However, the mechanism of action of some lipids is complex, and not all of them can be explained.…”
Section: Discussionmentioning
confidence: 99%